2021
DOI: 10.4171/rmi/1315
|View full text |Cite
|
Sign up to set email alerts
|

Closed $G_2$-eigenforms and exact $G_2$-structures

Abstract: A study is made of left-invariant G 2 -structures with an exact 3-form on a Lie group G whose Lie algebra g admits a codimension-one nilpotent ideal h. It is shown that such a Lie group G cannot admit a left-invariant closed G 2 -eigenform for the Laplacian and that any compact solvmanifold nG arising from G does not admit an (invariant) exact G 2 -structure. We also classify the seven-dimensional Lie algebras g with codimension-one ideal equal to the complex Heisenberg Lie algebra which admit exact G 2 -struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In [10], M. Fernández and the first and third named author of this paper proved that there are no compact examples of the form (Γ�G, ) , where G is a simply connected solvable Lie group with (2, 3)-trivial Lie algebra , namely b 2 ( ) = 0 = b 3 ( ) , Γ ⊂ G is a cocompact discrete subgroup (lattice), and is an invariant exact G 2 -structure on Γ�G , namely it is induced by a left-invariant exact G 2 -structure on G . In [13], Freibert and Salamon showed that the same conclusion holds, more generally, when the Lie algebra of G admits a codimension-one nilpotent ideal.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…In [10], M. Fernández and the first and third named author of this paper proved that there are no compact examples of the form (Γ�G, ) , where G is a simply connected solvable Lie group with (2, 3)-trivial Lie algebra , namely b 2 ( ) = 0 = b 3 ( ) , Γ ⊂ G is a cocompact discrete subgroup (lattice), and is an invariant exact G 2 -structure on Γ�G , namely it is induced by a left-invariant exact G 2 -structure on G . In [13], Freibert and Salamon showed that the same conclusion holds, more generally, when the Lie algebra of G admits a codimension-one nilpotent ideal.…”
Section: Introductionmentioning
confidence: 76%
“…Assume now that is an exact G 2 -structure on = ⋊ D ℝ , namely 𝜑 = d α for some α ∈ Λ 2 * . By [13], we know that if is strongly unimodular, then the solvable ideal is not nilpotent.…”
Section: Definition 31mentioning
confidence: 99%
See 2 more Smart Citations